PRINCIPLES OF PHASE-LOCKED LOOPS MATHEMATICAL MODELS CONSTRUCTION - M. P. Batura; A. P. Kuznetsov; L. Yu. Shilin; D. P. Kukin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of various embodiments study of the hardware and software phase-locked loops, suggesting possible variants of generalized mathematical models of the multi-systems as well as devices with a cyclic interrupt mode-locked are presented. One of the possible algorithms of phase-locked loops software functioning is offered.